Low temperature pvd alternative to cladding of wind turbine pin shaft coating method

CN123005291APending Publication Date: 2026-10-30DELIJIA TRANSMISSION TECH (JIANGSU CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611359016.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]然而,激光熔覆属于高温工艺,在实际应用中存在以下固有缺陷:熔覆层易产生气孔、裂纹等冶金缺陷,且涂层与基材的结合力不稳定;高温过程易导致40Cr基材热变形及组织变化,影响销轴的尺寸精度与疲劳性能;铜合金本身硬度较低,在转运装配途中易因磕碰划伤而造成产品报废;熔覆层的高温软化倾向及耐磨、抗咬合性能不足,难以适配陆上及海上风电的长寿命设计要求

Benefits of technology

(1)本发明通过低温PVD气相沉积结合基于涂层与基材物理化学响应差异的非机械选择性去除,在避免40Cr基材热变形的使过盈沉积区域的配合尺寸能够恢复至预设装配公差范围,且避免了传统机械加工导致的超硬涂层崩裂、剥落及基材损伤,实现了从熔覆工艺向低温PVD工艺替代后的尺寸精度自洽恢复;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123005291A_ABST
    Figure CN123005291A_ABST
Patent Text Reader

Abstract

The application discloses a wind power pin shaft coating method for replacing cladding by low-temperature PVD, and relates to the technical field of pin shaft coating, and comprises the following steps: obtaining an active surface suitable for PVD deposition; forming a DLC or WCC superhard coating on at least one fitting area surface of the pin shaft by low-temperature PVD gas phase deposition, forming an interference deposition; applying a non-mechanical energy field to the interference deposition area, and performing selective material removal; and controlling the progress of the selective material removal until the size of the fitting area is restored to a preset assembly tolerance range. By means of low-temperature PVD gas phase deposition and non-mechanical selective removal based on the difference in the physical and chemical responses of the coating and the base material, the fitting size of the interference deposition area can be restored to the preset assembly tolerance range, the thermal deformation of the 40Cr base material is avoided, the superhard coating is prevented from being cracked and peeled off and the base material is prevented from being damaged due to traditional mechanical processing, and the size precision is self-consistently restored after the low-temperature PVD process replaces the cladding process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of pin coating technology, and in particular to a low-temperature PVD alternative to cladding method for wind power pin coating. Background Technology

[0002] The sliding bearing pins of planetary gears in wind turbine gearboxes are key components for transmitting torque and bearing impact, operating under harsh conditions of heavy loads, boundary lubrication, and salt spray corrosion. To improve the friction reduction, wear resistance, and anti-galling properties of the pin mating area, existing technologies often employ laser cladding of copper alloys (such as CuSi12Ni2) for surface modification.

[0003] However, laser cladding is a high-temperature process, which has the following inherent defects in practical applications: the cladding layer is prone to metallurgical defects such as pores and cracks, and the bonding force between the coating and the substrate is unstable; the high-temperature process can easily cause thermal deformation and microstructure changes in the 40Cr substrate, affecting the dimensional accuracy and fatigue performance of the pin; the copper alloy itself has low hardness, and the product is easily scrapped due to bumps and scratches during transportation and assembly; the high-temperature softening tendency of the cladding layer and its insufficient wear resistance and anti-galling properties make it difficult to meet the long-life design requirements of onshore and offshore wind power.

[0004] To overcome the performance limitations of the aforementioned copper-based surface modifications, the use of low-temperature physical vapor deposition (PVD) technology to prepare ultra-hard coatings such as diamond-like carbon (DLC) or tungsten carbide carbon (WCC) on the pin surface has become an important technological alternative. This technology can be implemented at temperatures below 200°C, significantly improving surface hardness, reducing the coefficient of friction, and fundamentally preventing thermal deformation of the substrate.

[0005] However, when applying the aforementioned low-temperature PVD process to wind turbine large aspect ratio pins, the PVD-deposited coating thickness typically needs to reach a specific target value to ensure the wear resistance of the mating area during service. This thickness often causes the mating dimensions of the mating area to exceed the preset assembly tolerance range, resulting in interference fit. Since the hardness of DLC and WCC coatings is much higher than that of conventional tool materials, traditional machining methods (such as grinding and cutting) are very prone to causing coating cracking, peeling, or substrate damage when removing the interference fit, making it impossible to directly apply existing cladding layer machining repair processes.

[0006] Furthermore, due to the curved surface / internal hole structure and plasma field distribution characteristics of the large aspect ratio pin, the PVD deposited coating exhibits spatial thickness non-uniformity. When using non-mechanical energy fields (such as electrochemical or magnetic fields) to remove the interference fit, the intensity of the energy field on the pin surface also varies spatially. Existing technologies lack systematic compensation methods for these process uncertainties, leading to asynchronous removal processes at different locations during non-mechanical removal, making it difficult to achieve synchronous restoration of the mating area to the preset assembly tolerance range. Summary of the Invention

[0007] The purpose of this invention is to provide a low-temperature PVD alternative to cladding for wind turbine pin coating, in order to solve the problems mentioned in the background art.

[0008] To achieve the above objectives, the present invention provides the following technical solution: a method for low-temperature PVD coating as an alternative to cladding for wind turbine pins, comprising the following steps: The 40Cr wind turbine pin shaft is pretreated to obtain an active surface suitable for PVD deposition; A DLC or WCC superhard coating is formed on the surface of at least one mating area of ​​the pin by low-temperature PVD vapor deposition. The coating thickness of the mating area causes the mating dimensions of the mating area to exceed the preset assembly tolerance range, forming an interference fit. Based on the difference in physicochemical response caused by the difference in material properties between the superhard coating and the 40Cr substrate, a non-mechanical energy field is applied to the interference-deposited region to selectively remove materials. The process of selective material removal is controlled until the dimensions of the mating area are restored to the preset assembly tolerance range; The non-mechanical energy field is configured to preferentially act on the interference-deposited region, and the surface integrity of the superhard coating is not inferior to that of the deposited state.

[0009] Preferably, the substrate pretreatment includes removing the oxide layer and organic contaminant layer from the pin surface, exposing the 40Cr substrate to a clean metal surface, so as to stably exhibit the physicochemical response difference between the superhard coating and the 40Cr substrate during the subsequent selective material removal process.

[0010] Preferably, during the low-temperature PVD vapor deposition process, the thickness distribution of the superhard coating on the pin surface is controlled by at least one of the following means: local shielding, workpiece and target relative pose control, or plasma density field control, so that the interference deposition is concentrated in the mating area, while the non-matting area of ​​the pin does not form interference deposition or only forms a thin coating deposition.

[0011] Preferably, before applying the non-mechanical energy field, the outer surface of the pin is divided into a low-friction fit area and a non-essential coating area according to the assembly relationship between the pin and the inner hole of the planetary gear in the wind turbine gearbox, the cage and the spacer. The selective material removal is performed only on the interference deposit of the low-friction fit area.

[0012] Preferably, the non-mechanical energy field is an electrochemical energy field, the superhard coating is a WCC coating, and the selective material removal is based on the difference in electrochemical response between the WCC coating and the 40Cr substrate in the electrolyte, applying selective electrochemical action to the interference-deposited region to achieve material removal from the interference-deposited region.

[0013] Preferably, the non-mechanical energy field is a magnetic field, and the selective material removal utilizes the difference in magnetic permeability between the 40Cr substrate and the superhard coating, and / or utilizes the selective grinding effect of an external magnetic abrasive on the superhard coating, thereby achieving selective material removal of the interference-deposited area through magnetic drive.

[0014] Preferably, the selective material removal includes a first removal stage and a second removal stage; obtaining the current remaining amount of the interference deposit; when the current remaining amount is greater than a first threshold, performing the first removal stage with a first removal parameter; when the current remaining amount is less than or equal to the first threshold, switching to the second removal parameter to perform the second removal stage; the material removal rate corresponding to the first removal parameter is a first rate V1, and the material removal rate corresponding to the second removal parameter is a second rate V2, wherein V1 is higher than V2.

[0015] Preferably, the first threshold is configured as the critical interference thickness. The Not less than , and The sum of; among which, The thickness uniformity of the superhard coating is extremely poor. This is the equivalent thickness corresponding to the uniformity deviation caused by the non-mechanical energy field. This is the minimum controllable removal thickness for the second removal stage; The above With the All of these are dimensional parameters of thickness along the normal of the mating region; The system is configured such that at the end of the first removal stage, the remaining interference at each location on the mating area surface falls within a finishing range above the upper limit of the preset assembly tolerance range, and the lower limit of the finishing range is not less than the [preset tolerance range]. .

[0016] Preferably, in the second removal stage, the surface integrity parameters of the mating region are periodically checked; the second threshold is the allowable degradation increment. When the real-time degradation increment of the surface integrity parameter reaches the specified value... If the second removal stage is interrupted or the second removal parameter is reduced, the second removal stage is continued with a lower removal parameter after the deterioration trend of the surface integrity parameter is contained and stabilized, until the size of the mating area is restored to the preset assembly tolerance range.

[0017] Preferably, the substrate pretreatment, the low-temperature PVD vapor deposition, and the selective material removal constitute a synergistic process sequence; the surface roughness and cleanliness obtained by the substrate pretreatment are configured as conditions to ensure the deposition quality of the superhard coating, and the deposition quality of the superhard coating is configured as conditions to ensure the interface stability between the superhard coating and the 40Cr substrate during the selective material removal process.

[0018] The technical effects and advantages of this invention are as follows: (1) This invention combines low-temperature PVD vapor deposition with non-mechanical selective removal based on the difference in physicochemical response between the coating and the substrate. This avoids thermal deformation of the 40Cr substrate and allows the fit dimensions of the interference deposition area to be restored to the preset assembly tolerance range. It also avoids the cracking, peeling and substrate damage caused by traditional machining of the superhard coating. This invention achieves self-consistent restoration of dimensional accuracy after the replacement of the cladding process with the low-temperature PVD process. (2) This invention compensates for the inconsistency in the removal process caused by the differences in coating thickness and energy field intensity at different spatial locations in the mating area by configuring the first threshold as the equivalent thickness equivalent corresponding to the extreme deviation of the coating thickness uniformity deviation, the uniformity deviation of the non-mechanical energy field effect, and the combined effect of the minimum controllable removal thickness in the second removal stage. This ensures that at the end of the first removal stage, the remaining interference at each location on the surface of the mating area falls within the fine-tuning range above the upper limit of the preset assembly tolerance range, and the lower limit of the fine-tuning range is not less than the minimum controllable removal thickness in the second removal stage, thereby achieving synchronous precision dimensional recovery of the entire mating area and avoiding local over-removal or under-removal. (3) In the second removal stage, the present invention periodically checks the surface integrity parameters and uses the allowable degradation increment as a second threshold for feedback control. When the degradation trend of the surface integrity parameters reaches the threshold, the removal parameters are interrupted or reduced. After the degradation trend is contained and stabilized, the removal is continued with lower removal parameters. This dynamic feedback mechanism protects the surface integrity of the coating in real time during the finishing process, ensuring that the surface integrity of the mating area after final restoration is not inferior to that of the deposited state, and avoiding microcracks, peeling, or roughness degradation caused by parameter runaway during non-mechanical removal. (4) This invention employs a synergistic process sequence of substrate pretreatment, low-temperature PVD vapor deposition, and selective material removal. This ensures that the surface roughness and cleanliness obtained from the pretreatment guarantee the coating deposition quality, while the coating deposition quality in turn ensures the interfacial stability between the coating and the substrate during the removal process. By using local masking, workpiece and target relative pose control, or plasma density field control, interference deposition is concentrated in the low-friction mating region, while non-matting regions do not form interference deposition or only form a thin coating deposition. This reduces material consumption and subsequent processing burden in unnecessary coating areas, lowers the risk of assembly interference, and ensures the stability and consistency of the entire process chain. Attached Figure Description

[0019] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the embodiments of the invention to explain the invention, but do not constitute a limitation thereof. In the drawings: Figure 1 This is a schematic diagram of the pin coating method of the present invention. Detailed Implementation

[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] This invention provides, for example Figure 1 The method shown is a low-temperature PVD (physical vapor deposition) alternative to cladding coating for wind turbine pins. A DLC (diamond-like carbon) or WCC (tungsten carbide carbon) superhard coating is formed on the mating area of ​​a 40Cr wind turbine pin by low-temperature PVD vapor deposition. Based on the difference in physicochemical response between the coating and the substrate, a non-mechanical energy field is applied to the interference-deposited area to selectively remove the material, so that the size of the mating area is restored to the preset assembly tolerance range.

[0022] Example 1: WCC Coating and Electrochemical Selective Removal This embodiment discloses a basic process sequence for restoring the accuracy of interference deposition by combining WCC coating with electrochemical selective removal.

[0023] S1. Provide 40Cr wind turbine pins that have undergone quenching and tempering treatment. Use organic solvents for ultrasonic cleaning or alkaline solutions to remove oil and organic contaminants from the pin surface; use Ar⁺ (argon ion) glow discharge etching or bias sputtering etching to remove the surface oxide layer and adsorption layer, exposing a clean metal surface to the 40Cr substrate.

[0024] The surface roughness and cleanliness obtained from substrate pretreatment are configured as conditions to ensure the quality of subsequent PVD deposition: the removal of surface oxide layers and contaminants reduces interfacial defects between the coating and the substrate, and improves the adhesion of the WCC coating; while stable surface roughness is beneficial to maintaining the interfacial stability between the coating and the substrate during subsequent selective removal processes, and avoids interfacial delamination during electrochemical reactions.

[0025] S2. Using magnetron sputtering PVD or cathodic arc PVD, the deposition temperature is controlled below 200℃ to deposit a WCC coating on the surface of the pin mating area. During the deposition process, the target power, working gas pressure, and bias voltage are adjusted to make the WCC coating thickness in the mating area reach the target thickness. This target thickness causes the mating dimensions of the mating area to exceed the preset assembly tolerance range, forming an interference fit.

[0026] Low-temperature deposition conditions can prevent thermal deformation or microstructure transformation of 40Cr substrates, eliminating the problems of heat-affected zone and dimensional accuracy degradation caused by traditional high-temperature laser cladding processes.

[0027] S3. Based on the assembly relationship between the pin and the inner bore of the planetary gears, the cage, and the spacer in the wind turbine gearbox, the outer surface of the pin is divided into: a low-friction fit area and a non-essential coating area. The low-friction fit area is mainly the cylindrical surface area that forms a sliding fit with the inner bore of the planetary gears; the non-essential coating area includes the end face, the threaded area, and the non-critical contact area with the cage / spacer.

[0028] It was confirmed that the WCC coating thickness in the low-friction mating area had caused the mating dimensions in that area to exceed the preset assembly tolerance range, resulting in interference deposits.

[0029] S4. Immerse the low-friction mating area of ​​the pin coated with WCC into the electrolyte, or concentrate the selective electrochemical action in the interference-deposited area by local electrolyte shielding and electrode arrangement.

[0030] The electrolyte can be a neutral salt solution or a weakly alkaline solution, such as neutral salt solutions like sodium nitrate or sodium sulfate, or weakly alkaline solutions like dilute sodium hydroxide or sodium carbonate. Those skilled in the art can determine the specific electrolyte system and electrochemical conditions (such as current density, potential control mode, and reaction time) through conventional experiments based on the difference in electrochemical activity between the WCC coating and the 40Cr substrate in the target electrolyte. This ensures that selective electrochemical action preferentially acts on the WCC coating in the interference-deposited area, rather than corroding the 40Cr substrate.

[0031] The WCC coating material in the interference-deposited region is removed through selective electrochemical action, and the removal process is controlled until the dimensions of the low-friction mating area are restored to the preset assembly tolerances. During this process, a non-mechanical energy field is configured to preferentially act on the interference-deposited region, and the surface integrity of the WCC coating is not inferior to that of the deposited state.

[0032] S5, substrate pretreatment, low-temperature PVD vapor deposition, and selective material removal constitute a synergistic process sequence: the surface roughness and cleanliness obtained by substrate pretreatment ensure the deposition quality of the WCC coating; while the deposition quality of the WCC coating (including adhesion, density, and thickness uniformity) ensures the stability of the interface between the coating and the 40Cr substrate during selective removal, avoiding the entire coating peeling off or interface corrosion penetration during electrochemical action.

[0033] Example 2: Selective Removal Process Using Magnetic Fields This embodiment discloses a modified process for selective material removal using a magnetic field combined with magnetic abrasives, applicable to WCC coatings or DLC coatings.

[0034] S1. As in Example 1, the substrate pretreatment of the 40Cr pin shaft is completed, the low-temperature PVD vapor deposition of the WCC or DLC coating on the mating area surface is completed, and the low-friction mating area and the non-essential coating area are separated to form an interference fit.

[0035] S2. Use permanent magnets or electromagnets arranged circumferentially in the pin mating area to establish a non-uniform magnetic field or a controllable rotating magnetic field. Apply Fe3O4-based composite magnetic abrasive to the surface of the pin mating area in a suspension or dry manner.

[0036] By utilizing the difference in magnetic permeability between the 40Cr substrate and the WCC or DLC coating, and / or by utilizing the selective abrasive action of an external magnetic abrasive on the superhard coating, the magnetic abrasive is preferentially applied to the coating surface in the interference-deposited area under magnetic drive, thereby achieving selective material removal.

[0037] During the magnetic field selective removal process, the removal progress at each location in the mating zone is monitored by eddy current thickness measurement. When a certain area reaches the target size, the abrasive intensity in that area is reduced by adjusting the magnetic field distribution or the shielding method, so as to maintain the targeting of selective removal.

[0038] The magnetic field strength, magnetic abrasive particle size, and supply rate are determined by those skilled in the art through routine testing based on the interference deposition amount and target removal rate. The process of selective material removal is controlled until the mating area dimensions are restored to the preset assembly tolerance range.

[0039] Example 3: Zoned Deposition and Targeted Deposition Control in Coordination Zones This embodiment discloses a process control method that uses spatial selective deposition to concentrate interference deposition in the mating region, while non-matting regions do not form interference or only form a thin coating.

[0040] S1. As in Example 1, the 40Cr pin is degreased and ion-etched to obtain an active surface suitable for PVD deposition.

[0041] S2. Before performing PVD vapor deposition, based on the assembly relationship between the pin and the inner bore of the planetary gear in the wind turbine gearbox, the cage and the spacer, the outer surface of the pin is divided into a low-friction fit area and an unnecessary coating area.

[0042] In the low-temperature PVD vapor deposition process, the coating thickness distribution is controlled by at least one of the following methods: A jacket-type shielding sleeve, made of vacuum-compatible materials (such as stainless steel or molybdenum), is used to shield non-essential coating areas, exposing only low-friction mating areas for PVD deposition. Adjust the eccentricity between the pin's rotation axis and the target plane, or adjust the target-to-particle distance, so that the plasma density is focused in the low-friction mating region; The spatial distribution of plasma density can be controlled by adjusting the magnetic field strength or distribution of magnetron sputtering, or by using an auxiliary focusing coil.

[0043] By combining or using the above methods individually, the interference deposition of WCC or DLC coatings is concentrated in the low-friction mating area, while the non-matting area of ​​the pin does not form interference deposition, or only forms a thin coating deposition that does not cause the mating dimensions to exceed the preset assembly tolerance range.

[0044] S3. For the pins that have completed partitioned deposition, selective material removal and dimensional restoration are performed according to Example 1 (electrochemical removal, limited to WCC coating) or Example 2 (magnetic field removal, applicable to WCC or DLC coating).

[0045] Example 4: Two-stage parameterized removal control This embodiment discloses a method using critical interference thickness. The core method for two-stage progressive control of the selective material removal process is to use the first threshold and the allowable degradation increment ΔS_max as the second threshold.

[0046] S1. As in Example 1, the substrate pretreatment of the 40Cr pin shaft is completed, the low-temperature PVD vapor deposition of the WCC coating on the mating area surface is completed, and the low-friction mating area and the non-essential coating area are separated to form an interference fit.

[0047] S2. Using an eddy current thickness gauge, perform multi-point scanning along the axial direction of the mating area at preset intervals to obtain the current coating thickness at each location in the mating area. The detection parameters of the eddy current thickness gauge are determined through routine calibration based on the electromagnetic properties of the DLC or WCC coating.

[0048] The difference between the current coating thickness at each location and the target coating thickness (i.e., the critical coating thickness that will not cause the mating dimensions to exceed the preset assembly tolerance range) is used as the current interference at each location.

[0049] Under the condition of interference deposition, the current coating thickness at each mating zone is greater than the target coating thickness, thus ensuring that the current remaining amount is greater than zero. If eddy current thickness measurement finds a local thickness anomaly, the anomaly is excluded from the current remaining amount calculation, or additional deposition is performed in that area.

[0050] Extract the minimum value from the current interference at each position, and use it as the current remaining amount of interference deposition.

[0051] For process samples or first pieces from the same batch, cross-sectional metallographic microscopy measurements are performed to obtain direct measurements of the coating thickness, which are used to calibrate and verify the accuracy of eddy current thickness measurement data.

[0052] S3, The first threshold is configured as the critical interference thickness. . It is determined by the coupling of the following three dimensional thickness parameters along the normal of the mating region: (Extremely poor thickness uniformity deviation): Multiple measuring points are selected along the axial and circumferential directions on the surface of the mating area. The coating thickness at each point is obtained by eddy current thickness measurement or cross-sectional microscopy. The difference between the maximum and minimum values ​​is taken as the thickness of the coating. ; (Equivalent thickness equivalent to the uniformity deviation of the non-mechanical energy field): Using a standard test piece with the same material and coating as the pin, a removal calibration test was conducted under the same non-mechanical energy field conditions at the corresponding spatial positions of the simulated mating area (such as both ends, the middle, and the back target side). (For electrochemical energy fields, the same electrochemical action conditions were applied at different positions of the standard test piece in the electrolyte; for magnetic field energy fields, the same magnetic field and magnetic abrasive conditions were applied at different positions.) The difference in removal depth at each position within the same action time was measured, and the difference in removal depth at each position was directly used as the equivalent thickness equivalent. ; (Minimum controllable removal thickness in the second removal stage): Determined through process resolution calibration of the second removal stage. Specifically, the actual removal thickness is measured by applying a standard processing cycle or a fixed duration with the lowest energy field intensity required for effective removal in the second removal stage; or the change in removal thickness corresponding to a single parameter adjustment step size in the second removal stage is measured as... .

[0053] Critical interference thickness Determined according to the following conservative principles: Not less than , and The sum of these factors ensures that even if the mating area has a thinnest point in the coating and a weakest point in the energy field, at the end of the first removal stage, the remaining interference at each location on the surface of the mating area will still fall within the finishing range above the upper limit of the preset assembly tolerance, and the lower limit of the finishing range will not be less than [a certain value]. .

[0054] Combine the current remaining amount with Compare: When the current remaining amount is greater than At that time, the first removal stage is performed with the first removal parameter, and the material removal rate corresponding to the first removal parameter is the first rate V1; When the current remaining amount is less than or equal to When the second removal parameter is switched to execute the second removal stage, the material removal rate corresponding to the second removal parameter is the second rate V2.

[0055] V1 is higher than V2. The specific values ​​of V1 and V2 are determined by those skilled in the art through conventional experiments based on the total amount of interference deposition, process cycle requirements, and surface integrity constraints.

[0056] S4. In the second removal stage, the surface integrity parameters of the mating area are periodically checked at preset time intervals or removal progress intervals. Surface integrity parameters include, but are not limited to, surface roughness Ra (arithmetic mean roughness), microcrack density, or coating peeling area ratio.

[0057] The second threshold is the allowable increment of degradation. , is defined as the allowable increment of the surface integrity parameter relative to the depositional state reference value. The determination shall be made by those skilled in the art through routine testing based on the coating's service performance requirements and assembly quality requirements.

[0058] The increase in degradation obtained in this sampling inspection reached If necessary, interrupt the second removal stage or reduce the second removal parameter (e.g., further reduce V2 to a lower removal parameter V3).

[0059] Once the deterioration trend of the surface integrity parameter is contained and stabilized, that is, when the fluctuation range of the surface integrity parameter is less than the preset ratio in multiple consecutive sampling cycles (e.g., 2 to 3 cycles), or when the parameter value no longer shows a continuous upward trend, the second removal stage is continued with a lower removal parameter until the mating area size is restored to the preset assembly tolerance range.

[0060] Example 5: DLC Coating Modification Process This embodiment discloses a process path that replaces the WCC coating with a DLC coating and employs magnetic field selective removal, as a variation of the above embodiment.

[0061] S1. As in Example 1, the 40Cr pin is degreased and ion-etched to obtain an active surface suitable for PVD deposition.

[0062] S2. Using magnetron sputtering PVD, a DLC coating is deposited on the surface of the pin mating area using a graphite target at a temperature below 200°C. The deposition parameters are controlled so that the DLC coating thickness in the mating area exceeds the preset assembly tolerance range, forming an interference fit.

[0063] S3. As in Example 1, the outer surface of the pin is divided into a low-friction mating area and a non-necessary coating area according to the assembly relationship.

[0064] S4. Since DLC coatings typically exhibit insulating properties, electrochemical removal efficiency is low and the process window is difficult to control. Therefore, this embodiment does not employ electrochemical removal but instead uses a selective removal method combining a magnetic field with external magnetic abrasives: utilizing the difference in magnetic permeability between the 40Cr substrate and the DLC coating, and / or utilizing the selective grinding effect of magnetic abrasives on the DLC coating, selective material removal is performed on the interference-deposited area under magnetic drive.

[0065] S5. As in steps 2, 3, and 4 of Example 4, eddy current thickness measurement is used to obtain the current remaining amount (taking the minimum value of the current interference at each position and excluding local thickness anomalies). The detection parameters of the eddy current thickness gauge are determined by conventional calibration based on the electromagnetic properties of the DLC coating; according to... Not less than , and The sum determines the critical interference thickness, a two-stage switching between the first rate V1 and the second rate V2 is performed, and surface integrity parameters are periodically checked during the second removal stage to allow for incremental degradation. Feedback control is performed using a second threshold until the mating area size returns to the preset assembly tolerance range.

[0066] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for low-temperature PVD coating as an alternative to cladding for wind turbine shafts, characterized in that, Includes the following steps: The 40Cr wind turbine pin shaft is pretreated to obtain an active surface suitable for PVD deposition; A DLC or WCC superhard coating is formed on the surface of at least one mating area of ​​the pin by low-temperature PVD vapor deposition. The coating thickness of the mating area causes the mating dimensions of the mating area to exceed the preset assembly tolerance range, forming an interference fit. Based on the difference in physicochemical response caused by the difference in material properties between the superhard coating and the 40Cr substrate, a non-mechanical energy field is applied to the interference-deposited region to selectively remove materials. The process of selective material removal is controlled until the dimensions of the mating area are restored to the preset assembly tolerance range; The non-mechanical energy field is configured to preferentially act on the interference-deposited region, and the surface integrity of the superhard coating is not inferior to that of the deposited state.

2. The method for low-temperature PVD coating of wind turbine pins as an alternative to cladding according to claim 1, characterized in that, The substrate pretreatment includes removing the oxide layer and organic contaminant layer from the pin surface, exposing the 40Cr substrate to a clean metal surface, so as to stably exhibit the physicochemical response difference between the superhard coating and the 40Cr substrate during the subsequent selective material removal process.

3. The method for low-temperature PVD coating of wind turbine pins as an alternative to cladding according to claim 1, characterized in that, During the low-temperature PVD vapor deposition process, the thickness distribution of the superhard coating on the pin surface is controlled by at least one of the following methods: local shielding, workpiece and target relative pose control, or plasma density field control. This ensures that the interference deposition is concentrated in the mating area, while the non-matting area of ​​the pin does not form interference deposition or only forms a thin coating deposition.

4. The method for low-temperature PVD coating as an alternative to cladding for wind turbine pins according to claim 1, characterized in that, Before applying the non-mechanical energy field, the outer surface of the pin is divided into a low-friction fit area and an unnecessary coating area according to the assembly relationship between the pin and the inner hole of the planetary gear in the wind turbine gearbox, the cage and the spacer. The selective material removal is performed only on the interference deposit of the low-friction fit area.

5. The method for low-temperature PVD coating of wind turbine pins as an alternative to cladding according to claim 1, characterized in that, The non-mechanical energy field is an electrochemical energy field, the superhard coating is a WCC coating, and the selective material removal is based on the difference in electrochemical response between the WCC coating and the 40Cr substrate in the electrolyte, applying selective electrochemical action to the interference-deposited region to achieve material removal from the interference-deposited region.

6. The method for low-temperature PVD coating as an alternative to cladding for wind turbine shafts according to claim 1, characterized in that, The non-mechanical energy field is a magnetic field. The selective material removal utilizes the difference in magnetic permeability between the 40Cr substrate and the superhard coating, and / or utilizes the selective grinding effect of external magnetic abrasive on the superhard coating, thereby achieving selective material removal of the interference-deposited area through magnetic drive.

7. The method for low-temperature PVD coating of wind turbine pins as an alternative to cladding according to claim 1, characterized in that, The selective material removal includes a first removal stage and a second removal stage; the current remaining amount of the interference deposition is obtained; When the current remaining amount is greater than the first threshold, the first removal stage is performed with the first removal parameters; When the current remaining amount is less than or equal to the first threshold, the process switches to the second removal parameter to perform the second removal stage; the material removal rate corresponding to the first removal parameter is the first rate V1, and the material removal rate corresponding to the second removal parameter is the second rate V2, wherein V1 is higher than V2.

8. The method for low-temperature PVD coating of wind turbine pins as an alternative to cladding according to claim 7, characterized in that, The first threshold is configured as the critical interference thickness. ; Not less than , and The sum of; among which, The thickness uniformity of the superhard coating is extremely poor. This is the equivalent thickness corresponding to the uniformity deviation caused by the non-mechanical energy field. This is the minimum controllable removal thickness for the second removal stage; The above With the All of these are dimensional parameters of thickness along the normal of the mating region; The system is configured such that at the end of the first removal stage, the remaining interference at each location on the mating area surface falls within a finishing range above the upper limit of the preset assembly tolerance range, and the lower limit of the finishing range is not less than the [preset tolerance range]. .

9. A method for low-temperature PVD coating as an alternative to cladding for wind turbine shafts according to claim 7, characterized in that, In the second removal stage, the surface integrity parameters of the mating region are periodically checked; the second threshold is the allowable degradation increment. ; When the real-time degradation increment of the surface integrity parameter reaches the If necessary, interrupt the second removal phase or reduce the second removal parameters; Once the degradation trend of the surface integrity parameter is contained and stabilized, the second removal stage is continued with a lower removal parameter until the size of the mating area is restored to the preset assembly tolerance range.

10. A method for low-temperature PVD-based alternative cladding coating of wind turbine pins according to claim 1, characterized in that, The substrate pretreatment, the low-temperature PVD vapor deposition, and the selective material removal constitute a synergistic process sequence; the surface roughness and cleanliness obtained by the substrate pretreatment are configured as conditions to ensure the deposition quality of the superhard coating, and the deposition quality of the superhard coating is configured as conditions to ensure the interface stability between the superhard coating and the 40Cr substrate during the selective material removal process.